2016
DOI: 10.15405/epsbs.2016.08.59
|View full text |Cite
|
Sign up to set email alerts
|

The Innovation-Performance Linkage: Empirical Evidence of Malaysian Manufacturing SMEs

Abstract: It has long been acknowledged that SMEs contribute significantly to the overall economic performance in Malaysia. However, SMEs in Malaysia are yet to reach their full potential. To improve the performance of SMEs, understanding its drivers is crucial. Previous research found that organization which have a more innovative behavior are likely to initiate an organizational change that could affect organizational performance. Thus, the aim of this study is to investigate the relationship between organizational in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Innovative behaviour is the implementation of ideas, which grants firms a competitive advantage and higher profitability (Roberts & Amit, 2003). It has been shown in previous studies that innovation and firm performance have a positive relationship (Rosli & Sidek, 2013;Zakaria, Abdullah, & Yusoff, 2016). Ramamoorthy, Flood, Slattery, and Sardessai (2005) found that employees are likely to perform their job efficiently when they are in an environment that encourages innovative behaviour, thereby contributing to better company performance.…”
Section: Hypotheses Development and Theorymentioning
confidence: 99%
“…Innovative behaviour is the implementation of ideas, which grants firms a competitive advantage and higher profitability (Roberts & Amit, 2003). It has been shown in previous studies that innovation and firm performance have a positive relationship (Rosli & Sidek, 2013;Zakaria, Abdullah, & Yusoff, 2016). Ramamoorthy, Flood, Slattery, and Sardessai (2005) found that employees are likely to perform their job efficiently when they are in an environment that encourages innovative behaviour, thereby contributing to better company performance.…”
Section: Hypotheses Development and Theorymentioning
confidence: 99%
“…There are empirical evidences in existing literature that prove that performance relative to competitors is also a key measurement of business success for SMEs (Ahmad, 2007;Bocij, 2018). Moreover, Zakariaa et al (2016) have also used performance relative to competitors to access business success along with financial performance, non-financial performance, and business growth.…”
Section: Perceived Performance Relative To Competitorsmentioning
confidence: 99%
“…On the other hand, few researchers have focused on non-financial aspects (Haber & Reichel, 2005;Hoque, 2004). Moreover, some studies have considered growth of company as the parameter of business success (Ahmad, 2007) and others have deemed performance relative to competitors as determinant factor for business success (Zakariaa et al, 2016;Nzimande & Padayachee 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, SMEs can transform to be better in enhancing organization, management and production capabilities; improving productivity and efficiency; enabling better quality and monitoring; and developing innovators and producers of IR 4.0 technologies (MITI, 2018). However, SMEs in Malaysia are not yet reaching the full potential in improving the performance (Zakaria et al, 2016). Therefore, it is important to understand the drivers that can assist SMEs to fully contribute to the economic performance especially in innovation performance.…”
Section: Introductionmentioning
confidence: 99%